Design and Implementations of Control System Quadruped Robot Driver Application Based on Windows Platform - Made Sudarma; IBA Swamardika; IW Dani Pranata (Institute of Advanced Engineering and Science, 2015)
Wireless remote device control system is a controlling method which is widely used in various fields. By using wireless communication media, remote control system becomes more efficient and flexible. Computer application is one of the devices which can be used to perform remote controlling. Computer application can be made in accordance with the need of its users in conducting device controlling from the distance. Remote controlling is also can be applied on the robotic field. One of the examples is wireless remote controlling of Quadruped Robot. By utilizing its Windows application such as Visual Basic in order to establish communication with wireless communication module such as Xbee-PRO, a control system can be designed which can be used to control the movement of Quadruped Robot wirelessly. Wireless communication module is also has to be installed and able to perform data communication with the device to be controlled that is Quadruped Robot. The addition of camera which is also using wireless communication system will be very helpful for the users in knowing the condition around Quadruped Robot.